James C. Wright et al., The Mycenaean Settlement on Tsoungiza Hill (Nemea Valley Archaeological Project III). - Dickinson, Oliver (Journal of Greek Archaeology, 2021)
This pair of volumes complete the publication of the Bronze Age phases of the prehistoric site of Tsoungiza, close to the site of the sanctuary of Zeus at ancient Nemea, which in historical times hosted one of the major four panhellenic festivals of athletic games (Vol. I of the Project published the Early Bronze Age remains).